IMPLEMENTASI MEDIA PEMBELAJARAN ICT UNTUK MENINGKATKAN HASIL BELAJAR GEOGRAFI PADA SISWA SMA NEGERI 2 HALMAHERA TENGAH - Andi Suaema; Wati Ahmad (Universitas Khairun, 2023)
The success of learning carried out in an educational activity is how students can learn, by identifying, developing, organizing, and using all kinds of media and learning resources. The purpose of this study was to determine the implementation of ICT learning media in improving the learning outcomes of class X students in the subject of geography on cartography material at SMA Negeri 2 Halmahera Tengah. This type of research is classroom action research (CAR). The implementation of this research follows the stages of planning, implementing, observing, and reflecting according to Kemmis McTaggart. The research subjects were class X students of SMA Negeri 2 Halmahera Tengah. The results showed that the increase in learning outcomes in learning geography after using ICT learning media was in the first cycle, which obtained an average value of 64.44 with a mastery learning achievement of 72.22%. Whereas in cycle II, the average score was 80.55 with student learning completeness achieved at 94.44%. These results indicate that the use of ICT in geography learning can improve student learning outcomes.